MENINGKATKAN PEMAHAMAN SISWA PADA PEMBELAJARAN IPS DENGAN PENGGUNAAN METODE PEMECAHAN MASALAH - Lilis Nasriah (Universitas Sultan Ageng Tirtayasa, 2016)
This study aims to Improve Student understanding with the use of problem-solving method in social studies learning Class VII - D SMP Negeri 2 Tigaraksa in the academic year 2011- 2012. The method used in this study is a model of classroom action research . This research was conducted by 3 cycles of action . Each cycle includes the steps of: planning, implementation , observation , and reflection . The collection of data carried out by observation of learning outcomes and tes.Hasil research shows that learning to use the troubleshooting methods can enhance students' understanding . It can be seen from the success of students in each cycle increases , the success rate of students who reached KKM first cycle was 5.86% , 7.02% the second cycle and the third cycle of success reached 7.60%